Newest Trends and Technologies Related to Actuarial Mathematics - Review Paper (Balkan Journal of Applied Mathematics and Informatics, 2023)
This paper gives an overview of the new methods and the last trends considering actuarial mathematics. Based on a few papers that we consider relevant to our topic, we picked the information that is interesting to review. We will discuss different mathematical models and their use in the actuarial calculations for life insurance and non-life insurance